Marketing Strategy Implementation in Islamic Boarding Schools: A Study of 7P Marketing Mix in Blitar, Indonesia - Budiarti, Endah; Amin, Nor Fadila (Journal of Nonformal Education, 2025)
Background: Pesantren as an Islamic educational institution in Indonesia, faces challenges in maintaining and increasing competitiveness in the digital era. Marketing strategies are important to attract the interest of prospective students and ensure the sustainability of the pesantren. Research Objectives: This study aims to uncover and analyze the marketing strategies implemented by the Nurul Ulum Islamic Boarding School in Blitar City and the Nurus Salam Islamic Boarding School in Blitar Regency. Research Method: This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observations, and document studies, with purposive informant selection and snowball sampling. Data analysis was carried out using qualitative analysis techniques. Research Findings: The results of the study show that the two pesantren have implemented marketing strategies through various product offerings, but do not yet have a specific strategy for determining education costs (prices). The selection of a location (place) has been carried out, with the Nurul Ulum Islamic Boarding School benefiting more because of its strategic location. Promotions have not run optimally due to the absence of planning, limited budgets, and in-depth evaluation. Improving the quality of human resources (people) has been running, but the lack of performance evaluation is an obstacle. Physical evidence is adequate, although the Nurus Salam Islamic Boarding School still needs improvement. The education process has been running well, with the guidance of experts and regular activities.Conclusion: This study shows that although some aspects of marketing have been in line with the theory, there is still a need for improvement and development of specific strategies to achieve more optimal results.Novelty: This study provides a comprehensive overview of the marketing strategies implemented by two Islamic boarding schools in Blitar, focusing on analyzing each element of the marketing mix and identifying areas that need improvement. This research provides practical recommendations for Islamic boarding schools in developing more effective and sustainable marketing strategies.